WOMAN AS ACTRESS OF TRADITIONAL PERFORMING ARTS AND GENDER JUSTICE IN EAST JAVA - Wurianto, Arif Budi (JURNAL SATWIKA, 2017)
Main problem is whether gender justice and equality in art performance, mainly in traditional art performance, have become central issues in efforts to socialize and as a gender mainstream in Education, Law, Economy, Politic, and Social.   In general and traditional art performance, woman always involved, especially the main actresses in various art performances, they are adored both as ‘diva or idol’ who  are  able  to  attract  people  and  also  are  humiliated  because,  in  some occasions,  she  shows  her  over-sensuality  so  that  it  humiliates  her  dignity  as  a woman.  The  both  positions  generate  a  number  of  questions  about  position  of gender mainstream and its advocating.